Occurrence of ornithodoros brasiliensis aragão (acari: Argasidae) in São Francisco De Paula, RS, Southern Brazil - Martins, J. R. (2011)
There have been no reports of the endemic Ornithodoros brasiliensis (Aragão) in Rio Grande do Sul, southern Brazil, since the 1950s. In January 2007, 21 O. brasiliensis ticks were collected in a rural area named "Cruzinha" in the municipality of São Francisco de Paula, RS, and another population was sampled later that year (October) in Vargem do Cedro, another rural area of São Francisco de Paula, following reports of human parasitism by ticks. The reappearance of this tick is a reason for concern in terms of public health.